2015
DOI: 10.1371/journal.pone.0133044
|View full text |Cite
|
Sign up to set email alerts
|

Landscape Analysis of Adult Florida Panther Habitat

Abstract: Historically occurring throughout the southeastern United States, the Florida panther is now restricted to less than 5% of its historic range in one breeding population located in southern Florida. Using radio-telemetry data from 87 prime-aged (≥3 years old) adult panthers (35 males and 52 females) during the period 2004 through 2013 (28,720 radio-locations), we analyzed the characteristics of the occupied area and used those attributes in a random forest model to develop a predictive distribution map for resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 24 publications
0
30
0
Order By: Relevance
“…The modeled data in that study determined that males and females, and females with and without kittens exhibited distinctly different movement patterns, but did not specify if those different movements were within the same habitat types, as suggested by Frakes et al [7], or in different habitat types. Only one female panther carrying a GPS collar gave birth during the van de Kerk et al [23] study.…”
Section: Introductionmentioning
confidence: 84%
See 4 more Smart Citations
“…The modeled data in that study determined that males and females, and females with and without kittens exhibited distinctly different movement patterns, but did not specify if those different movements were within the same habitat types, as suggested by Frakes et al [7], or in different habitat types. Only one female panther carrying a GPS collar gave birth during the van de Kerk et al [23] study.…”
Section: Introductionmentioning
confidence: 84%
“…Our results suggest that the model developed by Frakes et al [7], for use by conservation agencies attempting to identify and protect the most valuable panther habitat in south Florida, should be modified to consider the influence of fractures on identifying and protecting habitat for the federally endangered Florida panther. This conclusion is supported by the fact that their model showed that hydrology is one of the most important factors determining the presence of adult panthers.…”
Section: Journal Of Geoscience and Environment Protectionmentioning
confidence: 92%
See 3 more Smart Citations